Synthesis of piperidine and pyrrolidine derivatives by electroreductive cyclization of imine with terminal dihaloalkanes in a flow microreactor - Naito, Yuki; Shida, Naoki; Atobe, Mahito (Beilstein Journal of Organic Chemistry, 2022)
We have successfully synthesized piperidine and pyrrolidine derivatives by electroreductive cyclization using readily available imine and terminal dihaloalkanes in a flow microreactor. Reduction of the substrate imine on the cathode proceeded efficiently due to the large specific surface area of the microreactor. This method provided target compounds in good yields compared to a conventional batch-type reaction. Furthermore, piperidine and pyrrolidine derivatives could be obtained on preparative scale by continuous electrolysis for approximately 1 hour.
Keywords: electrochemical synthesis; electrocyclization; flow microreactor; heterocyclic amines; imine